ANALISIS PUTUSAN PENOLAKAN PEMBATALAN MEREK “PIERRE CARDIN” - Irawan, Vania; Budiningsih, Catharina Ria (Faculty of Law, Parahyangan Catholic University, 2023)
Well-known trademarks are crucial to be protected because they are susceptible to infringement by third parties. Disputes concerning well-known trademarks are quite prevalent in Indonesia. One case involving a well-known trademark in Indonesia that is the focus of this research is the